2004
DOI: 10.1021/jm049970d
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Naive Bayes Classifier with Consensus Scoring Improves Enrichment of High-Throughput Docking Results

Abstract: We have previously shown that a machine learning technique can improve the enrichment of high-throughput docking (HTD) results. In the previous cases studied, however, the application of a naive Bayes classifier failed to improve enrichment for instances where HTD alone was unable to generate an acceptable enrichment. We present here a protocol to rescue poor docking results a priori using a combination of rank-by-median consensus scoring and naive Bayesian categorization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 11 publications
(18 reference statements)
0
61
0
Order By: Relevance
“…It has been reported that the median rank is more suitable than the average rank in consensus-scoring because the former is less sensitive to outliers [40].…”
Section: Consensus Scoringmentioning
confidence: 99%
“…It has been reported that the median rank is more suitable than the average rank in consensus-scoring because the former is less sensitive to outliers [40].…”
Section: Consensus Scoringmentioning
confidence: 99%
“…Substructural analysis was studied in considerable detail by workers at the National Institutes of Health in an extended programme to develop novel anti-cancer agents [47][48][49], and also by workers at Lederle [29] and Sheffield [50][51][52]. However, it is only in the last few years that this general approach has become widely used [53][54][55][56][57][58][59][60][61][62].…”
Section: Substructural Analysis Naive Bayesian Classifiers and Groupmentioning
confidence: 99%
“…66 Furthermore, the median rank is more suitable than the average rank in consensus-scoring because the former is less sensitive to outliers. 67 Rank by median consensus scoring was used in the in silico screening against plasmepsin and cathepsin B (Table 1). For plasmepsin, consensus scoring was preferred to ranking by LIECE because visual inspection of the best LIECE poses revealed several unlikely binding modes.…”
Section: Consensus Scoringmentioning
confidence: 99%